2009
DOI: 10.1021/bi900565t
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Folate Receptor Internalization by Protein Kinase C α

Abstract: The glycosyl-phosphatidylinositol anchored folate receptor (FR) mediates selective delivery of a broad range of experimental drugs to the receptor-rich tumors, but molecular mechanisms controlling FR internalization have not been adequately studied. FR quantitatively recycles between the cell surface and endocytic compartments via a Cdc42-dependent pinocytic pathway. Protein kinase C (PKC) activators including diacylglycerol and phorbol ester have previously been reported to increase the proportion of FR on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…For these experiments, cells were washed with acid-buffered (pH 3.5) saline, neutralized, then incubated with 50 nM [ 3 H]folic acid or [ 3 H] AGF154 at neutral pH (pH 7.4) (i) at 4°C to measure surface FRα-bound [ 3 H]substrate. Cells were also incubated at 37°C for 1 h, after which (ii) total cell-associated [ 3 H]substrate (includes sum of both [ 3 H]folic acid or [ 3 H] AGF154 bound to surface FRα and internalized [ 3 H]folic acid or [ 3 H] AGF154 ) and (iii) internalized [ 3 H]substrate were quantified (20, 34). For all treatments, parallel incubations were performed with 10 µM non-radioactive folic acid which competes with FR-mediated binding and uptake so as to identify the non-specific (non-FRα-mediated) radiolabeled fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these experiments, cells were washed with acid-buffered (pH 3.5) saline, neutralized, then incubated with 50 nM [ 3 H]folic acid or [ 3 H] AGF154 at neutral pH (pH 7.4) (i) at 4°C to measure surface FRα-bound [ 3 H]substrate. Cells were also incubated at 37°C for 1 h, after which (ii) total cell-associated [ 3 H]substrate (includes sum of both [ 3 H]folic acid or [ 3 H] AGF154 bound to surface FRα and internalized [ 3 H]folic acid or [ 3 H] AGF154 ) and (iii) internalized [ 3 H]substrate were quantified (20, 34). For all treatments, parallel incubations were performed with 10 µM non-radioactive folic acid which competes with FR-mediated binding and uptake so as to identify the non-specific (non-FRα-mediated) radiolabeled fraction.…”
Section: Resultsmentioning
confidence: 99%
“…For assays of FRα-mediated [ 3 H]folic acid and [ 3 H] AGF154 uptake by IGROV1 NTC and KD-4 and KD-10 FRα knockdown cells (34), cells were seeded at ∼0.8 × 10 6 cells/60 mm dish three days prior to experiment. For uptake assays, the cells were washed at room-temperature 3x with PBS, then washed 2x with acetate buffer (pH 3.5).…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of membrane staining, intracellular staining was rarely present. Intracellular staining for FRA is expected given that the receptor cycles, carrying folates with it, to the intracellular compartment while remaining membrane associated, by an endocytotic mechanism ([Elnakat et al 2009]).…”
Section: Resultsmentioning
confidence: 99%
“…Elnakat et al, [24] showed that Protein Kinase Cα (PKCα) substrate, annexin II, is required for FR internalization. When activated PKCα is recruited to FR-rich membrane caveolar microdomains, it inhibits FRα internalization.…”
Section: Reviewmentioning
confidence: 99%
“…Endocytosis of FRα is assisted by low-density lipoprotein (LDL) receptorrelated protein 2 (LRP2), a multifunctional cell-surface receptor expressed in the embryonic neuroepithelium [23] as well as by protein kinase Cα [24].…”
Section: Introductionmentioning
confidence: 99%